What Situation Do We Have In Health Care-Related Infections?: Evaluation of an Intensive Care Unit - Eşref Araç; Şafak Kaya; Serdar Almacıoğlu; Emrah Günay; Enver Yüksel; Mehmet Serdar Yıldırım; Songül Araç (Van Tıp Dergisi, 2019)
INTRODUCTION: The prevalence of SCI is higher in the ICUthan in other units of the hospital because of frequent central venous catheters, urinary catheters, mechanical ventilation and long-term hospitalizations. In addition, the use of broad spectrum antibiotics frequently causes colonization and infections with resistant microorganisms in patients in these units. This study was undertaken to describe the impact of various risk factors and the antibiotic resistance of breeding microorganisms in the SBIE epidemiology acquired in the ICU METHODS: A retrospective study was carried out on prospectively collected data of 62 patients who applied internally at tertiary ICU between January 2014 and December 2017. The SBIH was diagnosed according to the Centers for Disease and Control definitions. All patients' data were obtained from hospital information management system and infection control committee patient follow-up forms. RESULTS: 36 (58.1%) of the cases were male and 26 (41.9%) were female. The causative agent of infection is primarily A. baumannii, K. pneumoniae and E. coli. The most common infection was found as urinary tract infection with 34%. Ventilator-associated pneumonia and bloodstream infection were more frequent in patients who were mechanically ventilated, and this was statistically significant In our study, all A. baumannii strains were carbapenem resistant. TMethicillin resistance was present in all of the coagulase (-) staphylococci. DISCUSSION AND CONCLUSION: It is also evident that a larger scale of work with a larger number of patients are needed, although each hospital considers that such studies are important in terms of knowing the infection frequency, factors and resistance profile in their unit.